Exploring the Formation Mechanism of Cultural Differences Between Chinese and Western Competitive Sportsmanship: Based on a Qualitative Study - Luo, Changxin; Xu, Kuo; Liu, Shuchang; Zhu, Yuping; Zhang, Guodong (Quality in Sport, 2024)
Purpose: The development of athletics is pivotal to China's aspiration of becoming a modern competitive sports powerhouse. Spiritual culture, being its core component, also serves as an intrinsic driving force. A nuanced understanding of the formation of spiritual and cultural differences between Chinese and Western competitive sports is essential for the connotative construction of China's competitive sports strength. Methodology: This study employs qualitative text analysis to examine 46 texts in both Chinese and English. The aim is to investigate the mechanisms underlying the cultural differences between Chinese and Western sportsmanship and to construct a theoretical model. Findings: The study identifies five key dimensions—mindset, internal and external drive, traditional paradigm, code of conduct, and spiritual pillars—that collectively contribute to the cultural differences in Chinese and Western competitive sportsmanship. Among these, mindset, internal and external drive, and traditional paradigm are the causative factors, while codes of conduct and spiritual pillars represent the actions and outcomes that shape these cultural differences. Value: This study aims to elucidate the specific spiritual and cultural differences between Chinese and Western competitive sports, and the reasons behind these differences. By constructing a mechanism for the formation of these cultural differences, the study seeks to foster a conducive cultural environment for the development of competitive sports in China. This, in turn, is expected to accelerate China's transition from a major sports nation to a leading sports power on the global stage.